2022
DOI: 10.1111/jfb.15167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low‐dose Piscirickettsia salmonis infection on haematological‐biochemical blood parameters in Atlantic salmon (Salmo salar)

Abstract: Piscirickettsia salmonis is the etiological agent of Piscirickettsiosis, a severe disease that affects Atlantic salmon (Salmo salar) farmed in Chile and many other areas (Norway, Scotland, Ireland, Canada and the USA). This study investigated the effects of low‐dose P. salmonis infection (1 × 102 CFU/ml) on Atlantic salmon. In this study, we challenged fish with an isolated representative of the EM‐90 genogroup via intraperitoneal injection for 42 days. Infected fish displayed decreased haematocrit and haemogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 79 publications
(112 reference statements)
2
4
1
Order By: Relevance
“…The latter was to be expected since only a living pathogen provides its functional cellular machinery for the synthesis of hemolysins to be induced in P. salmonis, and consequently, the lysis of erythrocytes in Atlantic salmon (Salmo salar) (5), which could corroborate the anemia generated by Piscirickettsiosis (2). These results are not in agreement with what was previously published by Isla et al (41), who reported a decrease in hematocrit from day 7 to 28 post-inoculation with live P. salmonis. However, this may be correlated to the bacterial dose they administered (low dose) and the size of the used smolt specimens (60-70 g), compared with the post-smolt specimens (700 g) used in this study, according to the ranges determined by .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The latter was to be expected since only a living pathogen provides its functional cellular machinery for the synthesis of hemolysins to be induced in P. salmonis, and consequently, the lysis of erythrocytes in Atlantic salmon (Salmo salar) (5), which could corroborate the anemia generated by Piscirickettsiosis (2). These results are not in agreement with what was previously published by Isla et al (41), who reported a decrease in hematocrit from day 7 to 28 post-inoculation with live P. salmonis. However, this may be correlated to the bacterial dose they administered (low dose) and the size of the used smolt specimens (60-70 g), compared with the post-smolt specimens (700 g) used in this study, according to the ranges determined by .…”
Section: Discussioncontrasting
confidence: 99%
“…salmonis (3 dpi); however, this decrease was not statistically significant at 7 and 14 dpi. findings agree with previous reports on smolt specimens of Atlantic salmon (Salmo salar) inoculated with a low dose of live P. salmonis (41) and in Patagonian blennie (E. maclovinus) challenged with Francisella noatunensis subsp. Noatunensis (39), which is a facultative intracellular bacterial pathogen that have similarities in terms of pathogenesis with P. salmonis (45).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This phenomenon could indicate hepatocyte collapse during transportation, disrupting energy storage and metabolic functions in the crab hepatopancreatic system. 40 NADH dehydrogenase [ubiquinone] iron−sulfur protein 4 was downregulated in the FC/LC comparison and upregulated in the DC/FC comparison. In contrast, phytanoyl-CoA dioxygenase peroxisomal-like was upregulated in the FC/LC comparison and downregulated in the DC/LC and DC/FC comparisons.…”
Section: Metabolic Process-related Depsmentioning
confidence: 99%
“…Several studies have investigated aspects of the fish immune system [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], and examined hematological responses in vaccinated and infected fish species [ 30 , 31 ]. However, there are no studies assessing cell analysis and effective immunity in Atlantic salmon following M. viscosa infection.…”
Section: Introductionmentioning
confidence: 99%